THE ROLE OF ASEAN INTERGOVERNMENTAL COMMISSION ON HUMAN RIGHTS IN HANDLING THE ISLAMOPHOBIA IN MYANMAR ROHINGYA CASE - Arafah Regita Santoso; Firyal Akbar; Septian Yulyanto (Sociae Polites, 2022)
The 2017 Rohingya ethnic’s mass massacre that happened in Rakhine states, Myanmar had been paid ASEAN attention in which ASEAN has established a specific body that can handle the concerning matters in this case. This body is called AICHR (ASEAN Intergovernmental Commission on Human Rights), with its particular function to address human rights issues to maintain the harmony between goals and principles of ASEAN Charter. Concerning ASEAN Charter, surely, AICHR is expected to align with the non-intervention principle of ASEAN. Consequently, it is inevitable for AICHR to undergo this mission with uncertainty to decide AICHR’s way to handle this case. Through using the qualitative research method in this paper, we could at least understand this case easily by being described enough from our collected data, then synchronously we could picture these two major ideas in this paper, namely AICHR and ASEAN Way whether in a partial or impartial technique to know how AICHR contribute while under the influence of ASEAN Way in this Rohingya Case, and to thoroughly solve this Rohingya case, it is our main goal to make this paper as considerable as possible to be discussed.